Comparation of Earnings Quality Measures at Industries in the National Stock Exchange of India - Munjal, Shikhil; Singh, Gurcharan (Journal of Accounting, Business and Management (JABM), 2024)
Earnings quality has emerged as an important phenomenon for many types of investors looking to invest in stocks. There are different approaches to determine the level of earnings management in academic research on earnings quality. To quantify earnings quality, the present study used the four techniques suggested by Penman (2001), Barton and Simko (2002), Leuz et al. (2003), and Desai et al. (2006). Using a sample of 65 companies from six major industries on the National Stock Exchange over a 12-year period, this study seeks to determine whether there is any consistency among the four measures of earnings quality. The analysis showed that a single approach cannot be used to define an organization as high or low quality. Hence, this study sheds light on the inconsistency of earnings quality measurements and advises firm stakeholders to employ several indicators when making decisions. JEL Classification: G34; G38; M41